Personal Branding ala Generasi Digital: Kajian Tafsir Maqashid Terhadap Trend Flexing - Ika Hilmiatus Salamah; Muhammad Fadhil Wathani; Syahreza Badarul Ulum; Mokh Sya'roni (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2025)
The development of social media has given rise to the phenomenon of flexing as a form of self-expression in the contemporary era, where individuals deliberately show off their wealth, achievements, or luxurious lifestyles to build a self-image. This research aims to examine flexing within the framework of personal branding using a maqashid interpretation approach. The method used is library research and qualitative to trace the interpretation of verses related to the meaning of flexing. This research reveals three main findings, namely the meaning of flexing from the perspective of popular culture and social psychology, verses related to flexing in the review of maqashid interpretation and Maqashid-based personal branding solutions. The result, from the perspective of popular culture and social psychology, suggests that flexing serves as a display of wealth for social validation and as a manifestation of the need for others to recognize oneself. Based on the analysis of the Qur'anic verses (QS. Al-Hadid: 20, Luqman: 18, At-Takatsur: 1-2), flexing contradicts the principles of maqashid shari'ah, especially in the aspects of protecting religion (hifzh al-din), soul (hifzh al-nafs), intellect (hifzh al-aql), offspring (hifzh al-nasl), and property (hifzh al-mal). As a solution, personal branding can be applied in line with Islamic values by emphasizing the importance of self-authenticity, cultivating an attitude of gratitude, and creating content that has social benefits.